2019
DOI: 10.1093/ej/uez051
|View full text |Cite
|
Sign up to set email alerts
|

Are Policymakers Ambiguity Averse?*

Abstract: We investigate the ambiguity preferences of a unique sample of real-life policymakers at the Paris UN climate conference (COP21). We find that policymakers are generally ambiguity averse. Using a simple design, we are moreover able to show that these preferences are not necessarily due to an irrational behavior, but rather to intrinsic preferences over unknown probabilities. Exploring the heterogeneity within our sample, we also show that the country of origin and the degree of quantitative sophistication affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Π EE = 0), while to define ROCR (ROMU) we now require only one equality to hold, namely Π CR0 = 0 (Π M U 0 = 0). With such a definition of ROCR, focused on the simple task, 60% of our sample is indifferent between the simple and the compound risk (consistent with what is found in Berger and Bosetti, 2017). This is in contrast with the 39% of subjects who reduce the model uncertainty under the analogous simple task.…”
Section: Further Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Π EE = 0), while to define ROCR (ROMU) we now require only one equality to hold, namely Π CR0 = 0 (Π M U 0 = 0). With such a definition of ROCR, focused on the simple task, 60% of our sample is indifferent between the simple and the compound risk (consistent with what is found in Berger and Bosetti, 2017). This is in contrast with the 39% of subjects who reduce the model uncertainty under the analogous simple task.…”
Section: Further Resultssupporting
confidence: 82%
“…Relatedly, in an experiment with children, Prokosheva (2016) obtained a significant relationship between arithmetic test scores and compound risk reduction, while no such relationship was found between ambiguity neutrality and these scores. Finally, using designs closer to ours, Chew et al 2017and Berger and Bosetti (2017) extended the investigations to the role of model uncertainty. Whereas Chew et al (2017) observed very similar attitudes towards compound risk and model uncertainty, 8 Berger and Bosetti (2017) only reported a significant association between attitudes towards ambiguity and model uncertainty, but not between attitudes towards ambiguity and compound risk.…”
Section: Related Experimental Literaturementioning
confidence: 81%
“…(Yet, as argued previously, we did our best to avoid such a situation.) While this assumption is not strictly necessary when experts are dogmatic, as in the CE tasks (see subsequently and also Berger and Bosetti, 2019), it is required when a specific model of choice under uncertainty is considered. (For experimental evidence on the role of model misspecification, see Aydogan et al, 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in principle there is no reason to expect these two attitudes to be equal: a policy maker might well be more prone to face risk due to the intrinsic randomness of some events than to face model uncertainty due to a lack of, for example, scientific knowledge. Recent experimental evidence on both students and real-life policy makers shows that this is indeed the case (Berger and Bosetti, 2020). A policy maker fulfilling this condition will be more averse to model uncertainty than to risk and consequently will exhibit uncertainty (or ambiguity) aversion.…”
Section: Unanimity Preferencesmentioning
confidence: 93%